Sensitivity of a Large and Representative Sample of Antarctic Marine Invertebrates to Metals. (31st May 2019) - Kefford, Ben J.; King, Catherine K.; Wasley, Jane; Riddle, Martin J.; Nugegoda, Dayanthi
Abstract: There are limited data on the sensitivity to contaminants of marine organisms in polar regions. Consequently, assessments of the risk of contaminants to marine biota in polar environments typically include extrapolations from temperate and/or tropical species. This is problematic because the taxonomic composition of organisms differs between polar and temperate/tropical waters, and both the toxicity of chemicals and the physiology of organisms are very different at the stable low temperatures experienced in polar marine systems. Collecting high‐quality sensitivity data for a wide range of marine polar organisms using traditional toxicity assessment approaches is a time‐consuming and difficult process, especially in remote and hostile environments. We applied a rapid toxicity testing approach, which allowed a much larger number of species to be tested than would be possible with traditional toxicity test methods, albeit with lower replications and fewer exposure concentrations. With this rapid approach, sensitivity estimates are less precise, but more numerous. This is important when constructing species sensitivity distributions (SSDs), which aim to represent the sensitivity of communities. We determined the approximate sensitivity (4‐ and 10‐d median lethal concentration [LC50] values) of a large and representative sample of Antarctic marine invertebrates to copper (Cu), zinc (Zn), and cadmium (Cd). Up to 88 LC50 values (from 88 different taxa) were used in the construction of SSDs. The hazardous concentrations for 1% of taxa (HC1) based on 10‐d LC50 values were 37, 346, and 792 μg/L for Cu, Zn, and Cd, respectively. Our results provide a basis for estimating the risk of exposure to metals for a large representative sample of marine polar invertebrates. Environ Toxicol Chem 2019;38:1560–1568. © 2019 SETAC